Perception of physical competencies is related to the reaction time of civilian police of special operations units Percepção de Competências Físicas está relacionada ao tempo de reação de policiais civis de unidades de operações especiais Percepción de competencias físicas relacionada con el tiempo de reacción de policias civiles de unidades de operaciones especiales - Matias T.S.* (2016)
© 2016, Editorial Ciencias Medicas. All rights reserved.Introduction: evidences suggest that reaction time (RT) is a sensible variable in the performance and motivational predisposition assessment of police officers. Such motivational component may indicate the person’s ability perception to respond to specific demands, and it may present better responses to situations which requires speed and choice reaction time. Objective: our study aimed to determine the relationship between reaction time performance and physical competence perception of police officers at special operation units. Methods: a total of 22 police officers from Santa Catarina State, all of them, members of Special Operation Coordination (COPE), average age 34,5 ± 9,1 years-old, were investigated. Reaction time was investigated by Vienna Test System Software. Strength, flexibility, and aerobic endurance questions were used to evaluate physical competence perception. Assessment Questionnaire of Physical Activity was carried out to evaluate Physical activity level. Data was analized by descriptive and inferential statistics. Results: results indicated that physical competence perception is related to RT (r= -0,69; p< 0,001). As higher was perception, lower was RT. Flexibility (r= -0,50; p< 0,01) and aerobic endurance (r= -0,55; p< 0,001) perceptions were negatively related to RT. Physical activity practice was negatively related to RT (r= -0,48; p< 0,05) and weekly time exposed to physical activity leads to a higher perception of competence (r= 0,59; p< 0,01). Conclusion: physical competence perception is related to RT of Police Officers at Special Operation Units. A higher competence perception seems to influence police motivation and their performance. Perceptions are an emotional component and is related to a better cognitive processing, resulting in better RT.